PERATAAN LABA DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PERUSAHAAN MANUFAKTUR DI BEI - Zuhriya, Syaidhatus; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test the factors of firm size, return on Asset, financial leverage, net profit margin, operating profit margin, deviation standard, and price book value which are influence to the income smoothing. The income smoothing is measured by using eckel index. The quantitative research is used as the research type, the consumersâ good company which are listed in Indonesia Stock Exchange in the years of 2009-2013 are used as the research populations. The purposive sampling is used as the sample collection method with the numbers of samples are 35 companies (103 firm year) which are fulfilled to the criteria. The multiple regressions with the program of SPSS 2.0 version are used as the analysis technique. Based on the result of multiple regressions analysis show with the significance level of 5%, so that the result of the research shows that i.e. : 1) the firm size has no positive influence to the income smoothing, 2) Return On Assets has positive influence to the income smoothing, 3) Debt to Equity Ratio has positive influence to the income smoothing, 4) Net Profit Margin has no positive influence to the income smoothing, 5) Operating Profit Margin has no positive influence to the income smoothing, 6) the deviation standard has no positive influence to the income smoothing, 7) Price to Book Value has no positive influence to the income smoothing.Keywords: Income Smoothing, Profitability, Solvability, Stock Risk, Firm Value